(untitled) (Canberra, 1989)
The book looks at the use of Australian trees and shrubs through experimental use in China, Kenya, Thailand and Zimbabwe. It includes uses as fuel wood, essential oil production, fodder, nitrogen fixation and more. The book also examines suitability for the various regions discussed and includes termite susceptibility. Trees in the study include Eucalypts, Acacia, Melaleuca, Leptospermum as well as information on some lesser known species
Keywords: Forests and forestry,Multipurpose trees; Tropics,Australia